'Blackberrying in the Sun'? Modernism and the Ageing Woman in Rhys's Good Morning, Midnight, Woolf's Mrs Dalloway and Sackville-West's All Passion Spent. Issue 3 (2nd July 2016) - Renk, Kathleen Williams
Abstract: Jean Rhys, Virginia Woolf and Vita Sackville-West break with tradition in re-envisioning the aging woman. No longer content with representing the forlorn dowager or the redundant females of Gaskell's Cranford, these writers challenge earlier representations while also confronting modernism itself. Instead of focusing on youth, they 'make it [modernism] new' by carefully detailing the various ways ageism and sexism make us 'the other', as they speak out against the interlocking oppressions of ageism and sexism. Whereas Rhys underscores what it means to be an impoverished, aging woman, Woolf and Sackville-West shift their concerns to the ways in which their characters come to terms with aging. For Woolf, there is both a sense of mourning and a sense of celebration as Clarissa attempts to unite her world through her 'offering' of parties that 'defy' the Gods. In contrast, Sackville-West's dutiful Lady Slane claims her independence for the first time in her life, as she refuses the ways in which her children infantilize her.